Getting the irrigation statistics right. Issue 3 (4th May 2022) - Kumar, M. Dinesh; Sahasranaman, Meera; Verma, Mahendra Singh; Kumar, Saurabh; Narayanamoorthy, A.
ABSTRACT: This study examines the importance of generating proper water accounts for large gravity-based irrigation schemes in order to assess scheme performance. It shows how the use of simplistic criteria used to assess the performance of gravity-based irrigation schemes can lead to an underestimation of the role they play in enhancing food security and agricultural production in countries such as India, which has established a huge network of irrigation canals. The paper offers specific suggestions on improving irrigation statistics that, in turn, can help in better evaluation of the returns on investments of public surface irrigation schemes.